Risposte

2014-01-08T16:53:06+01:00
Tu che stai rispondendo ti prego aiutamiiii
2014-01-08T18:07:49+01:00
[(-2+5a+3b)+6:(-2+5a+3b)+3]:[(-2+5a+5a+3b)]+2=
[-2+5a+3b+6x(-1/2+1/5a-1+1/3b-1)+3]:[-2+5a+3b+2+(-2+5a+3b)]+2=
[-2+5a+3b+(-3+6/5a-12b-1)+3]:[-2+5a+3b+2-2+5a+3b]+2=
[-2+5a+3b-3+6/5a-1+3]:10a+6b-2]+2=
[5a+3b+6/5a-1+2b-1-2]:[10a+6b-2]+2=
[5a+3b+6/5a-1+2b-1-2]x[+1/10a-1+1/6b-1-1/2]+2=
(+1/2+5/6ab-1-5/2a+3/10a-1b+1/2-3/2b+3/25a-2+1/5-1b-1-3/5a-1b-1+1/3-2-b-1-1/5a-1-1/3b-1+1)+2=
+1/2+5/6ab-1-5/2a+3/10a-1b+1/2-3/2b+3/25a-2+1/5a-2+1/5a-1b-3/5a-1b+1/5a-1+1/5-1b-1+1/3b-2-b-1-1/5a-1-1/3b-1+1+2=
-1-1/2a+3/10a-1b-3/2b+3/25+2/5+4/5+1/3+4/3+8:2=
-1-5/2+3/10a-1b-3/1b+3/25+2/5+4/5+1/3+4/3+4=
-1-5/2a+3/10a-1b-3/2b+524/75 = -1-5/2a+3/10a-1b-3/2b+524/75